Relevansi Dan Implementasi Teori Experiential Learning Kolb Dalam Konteks Pendidikan Kontemporer - Ilham Akbar (PT. Nawa Edukasi Nusantara, 2025)
Contemporary education faces significant challenges amid digital transformation and the demand for 21st-century skills. Traditional instructional models, still prevalent in many schools, are increasingly seen as inadequate in fostering adaptive, collaborative, and reflective learners. This study aims to analyze the relevance and implementation of David A. Kolb’s Experiential Learning Theory (ELT) in the Indonesian educational context. Using a descriptive qualitative method through library research, the study reviewed scientific sources published within the last five years (2021–2025). The findings indicate that ELT is highly relevant in promoting active, reflective, and contextual learning that places learners at the center. The implementation of ELT has shown significant impacts on improving learning motivation, critical thinking, and students' social competencies. However, challenges remain, including limited teacher understanding, inadequate facilities, and the dominance of conventional instructional culture. The study recommends strategic measures such as teacher capacity building, curriculum revitalization, cross-sector collaboration, and evaluation reform to support the widespread and sustainable adoption of experiential learning in Indonesia.